2018
DOI: 10.31234/osf.io/xkufm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual contributions to racial bias in pain recognition

Abstract: The pain of Black Americans is systematically under-diagnosed and under-treated, compared to the pain of their White counterparts. Extensive research has examined the psychological factors that might account for such biases, including status judgments, racial prejudice, and stereotypes about biological differences between Blacks and Whites. Across seven experiments we accumulated evidence that lower-level perceptual processes also uniquely contribute to downstream racial biases in pain recognition. We repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 0 publications
1
32
2
Order By: Relevance
“…One recent study found that White participants require more evidence to recognize pain in Black American faces compared with White American faces. 16 This in-group bias parallels a large literature on biased emotion perception in the United States 9 and directly links with the pain disparities mentioned above. Furthermore, it is still unknown if there are cultural or ethnic differences in the expression of pain.…”
Section: Letter To Editorsupporting
confidence: 57%
See 1 more Smart Citation
“…One recent study found that White participants require more evidence to recognize pain in Black American faces compared with White American faces. 16 This in-group bias parallels a large literature on biased emotion perception in the United States 9 and directly links with the pain disparities mentioned above. Furthermore, it is still unknown if there are cultural or ethnic differences in the expression of pain.…”
Section: Letter To Editorsupporting
confidence: 57%
“…Although researchers have begun to look for mechanisms underlying health inequities in pain, 6,12,16 a lack of diverse samples and over‐reliance on White stimulus sets has limited researchers' ability to evaluate whether facial expressions or their assessment contribute to disparities in pain. One recent study found that White participants require more evidence to recognize pain in Black American faces compared with White American faces.…”
Section: Letter To Editormentioning
confidence: 99%
“…Because of this diversity, researchers may better examine how pain-related outcomes vary based on these sociodemographic variables, promoting better understanding of disparities in pain care. 19 Indeed, stimuli from the DPD have been used to demonstrate that racial bias in pain perception facilitates disparities in treatment in white perceivers, 56 and further, that racial bias in pain perception is exacerbated by bottom-up and top-down cues to racial prototypicality. 20…”
Section: Discussionmentioning
confidence: 99%
“…One may circumvent this limitation by morphing neutral and painful images from the DPD to create dynamic expressions. 20 , 56 Using morphing software, a researcher can produce morphs representing points along the continuum from one face to another or generate a video transitioning from a neutral face to a painful face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation